2016
DOI: 10.15649/cuidarte.v7i1.303
|View full text |Cite
|
Sign up to set email alerts
|

Brinquedo terapêutico no procedimento de punção venosa: estratégia para reduzir alterações comportamentais

Abstract: Introdução: A enfermagem pediátrica deve estar atenta aos subsídios da assistência que tornem possível um melhor manejo da dor e da ansiedade oriundas da hospitalização infantil, geralmente, causadas pela realização de procedimentos invasivos como a punção venosa. O uso do Brinquedo Terapêutico Instrucional (BTI) pode representar uma intervenção eficaz para lidar com os efeitos negativos da hospitalização. Objetivo: Comparar as reações manifestadas pela criança frente ao preparo para punção venosa antes e após… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
38

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 21 publications
0
21
0
38
Order By: Relevance
“…4 In this study, the use of TP is highlighted by the students as an effective strategy for communication between the professional and the child, in accordance with other studies which emphasize TP as an important strategy for communication with the child. 6,27,28 The results revealed that the students are introduced to TP in the second year of their course, complying with the COREN-SP Recommendation that its teaching should be guaranteed in undergraduate courses, 16 and with COFEN Resolution 295/2004, 18 which ensures the nurse the skill for using this intervention in her care practice for the child and the family -for which, it is necessary for it to be taught and learnt.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…4 In this study, the use of TP is highlighted by the students as an effective strategy for communication between the professional and the child, in accordance with other studies which emphasize TP as an important strategy for communication with the child. 6,27,28 The results revealed that the students are introduced to TP in the second year of their course, complying with the COREN-SP Recommendation that its teaching should be guaranteed in undergraduate courses, 16 and with COFEN Resolution 295/2004, 18 which ensures the nurse the skill for using this intervention in her care practice for the child and the family -for which, it is necessary for it to be taught and learnt.…”
Section: Discussionmentioning
confidence: 83%
“…4,5 Regarding communication with children, one of the methods which deserves to be highlighted in the literature is Therapeutic Play (TP), which is used by nurses for explaining to children the procedures which they will undergo, in addition to helping them to manifest their feelings in relation to unknown and uncomfortable situations, as in the example of the illness and their hospitalization. 3,6,7 Its use by the nurse in providing pediatric care is permeated by numerous benefits, not only for the child -who comes to comprehend better what is happening to her, becoming more calm, secure and collaborative -but also for the family, the nurse, the team and the care environment. 7 In the international literature, its use is highlighted as having a high therapeutic value for the child, contributing not only to physical improvement but also to the child's emotional well-being, 8 to reduction in pain and stress related to experiencing procedures such as venipuncture, 9 dressings, 10 inhalation therapies, 11 radiotherapy 12 and the preparation for surgery, 13,14 among others; it also has an effect on the reduction of the parents' anxiety, who come to understand this intervention's value.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this reality, although nurses and nursing graduates are able to recognize the importance of playing, few are those who systematically apply this activity. 12 Bearing this in mind, the content on TP should be addressed in undergraduate and its application stimulated in the practical field in pediatrics, as evidenced in a research with nursing students of a public university of São Paulo. In it, undergraduates affirm that teachers charge the theory of TP, but in practice, it is not done and added to the lack of stimulation, since, when stimulated, it favors awareness of its use.…”
Section: Discussionmentioning
confidence: 99%
“…Para tanto, a equipe de enfermagem deve compreender a necessidade de uma abordagem diferenciada ao público infantil, com a preparação para exames e procedimentos através do brinquedo terapêutico e abordagem adequada à fase de crescimento e desenvolvimento com envolvimento ativo do acompanhante 8 .…”
Section: Participação Do Acompanhante Na Assistência à Criança: Aspecunclassified
“…Além da competência técnico-científica para atender às necessidades decorrentes do diagnóstico e terapêutica, deve-se utilizar de subsídios que reflitam acerca das próprias ações a fim de possibilitar o estabelecimento de relações interpessoais efetivas para compreender pais e filhos como pessoas dotadas de demandas de cuidado 5 . Alguns instrumentos vem sendo utilizados como forma de aliviar as tensões causadas pela internação, pela mudança de ambiente e por estar cercada por pessoas estranhas, sendo eles o brinquedo terapêutico [6][7][8] , musicoterapia, estabelecimento de vínculo entre profissional-criança-acompanhante, e principalmente a presença do acompanhante na unidade 9 .…”
Section: Introductionunclassified